Geological Expeditions Organized in the Tashkent Oasis during the Colonial Period - Jamshid Pirimqulov (International Journal on Integrated Education, 2022)
The article is devoted to the geological expeditions of the colonial government carried out in the Tashkent oasis, which analyze the policy for the mastering of the natural resources of the region.